Peningkatan performa manajerial melalui budget planning: Literature review - Budianingsih, Trimulyani (Implementasi Manajemen & Kewirausahaan, 2022)
Organizations can be said to be successful if they have good performance. Empirical studies have proven that the creation of good performance is supported by many factors, one of which is budgeted planning. This study found that other factors affecting managerial performance are budget emphasis, budget participation, organizational commitment, differentiation strategy, organizational culture, leadership style, and many others. Based on the classification and type of budget, the budget is divided into several, namely short-term budget, long-term budget, fixed budget, flexible budget, zero-based budget, rolling budget, activity-based budgeting, incremental budgeting, planning, and programming budgeting systems. This literature review provides a contribution of thought that can be a reference for future researchers who want to conduct research and focus on performance with predictors of budget planning. Through this literature review, they can also get information and consider other constructs outside the budget planning construct.